2020
DOI: 10.1002/pc.25528
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics analysis of carbon fiber/epoxy microdroplet composite under UV light irradiation by micro‐Raman spectroscopy

Abstract: Evaluation of the surface morphology, chemical groups, interfacial microstructure, and mechanical properties of carbon fiber/epoxy resin microdroplet composites during ultraviolet photodegradation was carried out. The axial stress distribution and interfacial shear stress (ISS) distribution of the carbon fiber/microdroplet composite at 0.25% and 0.62% strains with different UV irradiation times were obtained using micro‐Raman spectroscopy. The results showed that after 40 hours of UV irradiation, tiny particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The carbon fabrics with or without aligned ZnO nanorods were characterized by Raman spectroscopy, and peaks at 330 cm −1 , 441 cm −1 , and 1,130 cm −1 confirmed that ZnO had been modified on the CF surface. Fu et al (2020) put CF/epoxy microdroplet composite exposed under UV irradiation and compared the Raman spectra of the aromatic group, methyl group, epoxy ring and aromatic ring under different times by micro-Raman spectroscopy. Frontiers in Materials frontiersin.org Zheng et al (2020) modified renewable cardanol onto CF surfaces by in situ polymerization to strengthen the fiber-matrix interface, and Raman spectroscopy was used to analyze untreated CF, CF-OH, and CF-cardanol surface structures (Figure 7A).…”
Section: Raman Spectroscopy (Raman)mentioning
confidence: 99%
“…The carbon fabrics with or without aligned ZnO nanorods were characterized by Raman spectroscopy, and peaks at 330 cm −1 , 441 cm −1 , and 1,130 cm −1 confirmed that ZnO had been modified on the CF surface. Fu et al (2020) put CF/epoxy microdroplet composite exposed under UV irradiation and compared the Raman spectra of the aromatic group, methyl group, epoxy ring and aromatic ring under different times by micro-Raman spectroscopy. Frontiers in Materials frontiersin.org Zheng et al (2020) modified renewable cardanol onto CF surfaces by in situ polymerization to strengthen the fiber-matrix interface, and Raman spectroscopy was used to analyze untreated CF, CF-OH, and CF-cardanol surface structures (Figure 7A).…”
Section: Raman Spectroscopy (Raman)mentioning
confidence: 99%